A case of endosalpingiosis in the lymph nodes of the mesocolon - Koichiro Niwa; Kazuhiro Sakamoto; Michitoshi Goto; Yutaka Kojima; Makoto Takahashi; Shun Ishiyama; Masaya Kawai; Yuu Okazawa; Natumi Tomita; Eiichiro Seki; Yuki Fukumura; Takashi Yao (Surgical Case Reports)
Abstract Background Endosalpingiosis in the lymph nodes of the mesocolon is very rare. We reported a case with appendiceal endometriosis who had endosalpingiosis in the lymph nodes of the mesocolon that was found during laparoscopic ileocecal resection. Case presentation The patient was a 44-year-old woman who had visited a physician for fever, bloody stool, and abdominal pain 1 year earlier. She was diagnosed with ulcerative colitis on colonoscopy, and symptoms improved with oral treatment. A colonoscopy performed 2 months after diagnosis detected a hard, 20-mm submucosal tumor (SMT) in the cecum. On abdominal contrast CT, an intensely stained mass, including a low-density region, was observed in the cecum. A boring biopsy was performed after mucosal resection of the cecal SMT at our hospital, but diagnosis could not be made. Since the possibility of a malignant lesion could not be ruled out, laparoscopic ileocecal resection was performed. In the resected specimen, a 29 × 27 × 21-mm mass was present in the appendicular root. On histopathological examination, appendiceal endometriosis and endosalpingiosis in the lymph nodes around the ileocolic artery were observed. The postoperative course was favorable, and the patient was discharged 7 days after surgery. Conclusion Differentiation of endosalpingiosis in lymph nodes in the mesocolon from lymph node metastasis of adenocarcinoma is important in patients with an abdominal mass.